Strong Convergence Theorem of Bregman Algorithm for Solving Variational Inequalities in Banach Spaces - Inkrong, Papatsara; Cholamjiak, Prasit; Wattanawitoon, Kriengsak; Witthayarat, Uamporn (Thai Journal of Mathematics, 2024)
Due to the significance of the variational inequality which related to solve various problems in other branches of sciences and engineering, in this paper, we introduce a new algorithm for finding solution of this problem by using Bregman method in real reflexive Banach spaces. Under some mild conditions, the convergence result is exactly proved. Our result improved and extended some previous results in the literature.